1997
DOI: 10.1002/j.1875-9114.1997.tb03703.x
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Asthma: The Effect of Estrogen on Symptoms, Pulmonary Function, and β2‐Receptors

Mary H.H. Chandler,
Sandra Schuldheisz,
Barbara A. Phillips
et al.

Abstract: Study Objectives. To characterize asthma symptoms, pulmonary function, and responsiveness to β2‐agonist stimulation, and in vitro β2‐receptor density and cyclic adenosine 3′,5′‐monophosphate (cAMP) response throughout the menstrual cycle in women with premenstrual asthma (PMA); and to examine the effect of exogenous estradiol administration on asthma symptoms, pulmonary function and responsiveness, and β2‐receptor density and function in these women.Design. Open‐label, longitudinal, 9‐week study.Setting. A uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A study reported that 30%-40% of asthmatic women experience worsening of their asthma symptoms before and during menstruation [ 29 ]. One third of women with asthma experience a large peak expiratory flow rate throughout the premenstrual and menstrual periods [ 30 ].…”
Section: Yoga Asana’s and Their Target Benefitsmentioning
confidence: 99%
“…A study reported that 30%-40% of asthmatic women experience worsening of their asthma symptoms before and during menstruation [ 29 ]. One third of women with asthma experience a large peak expiratory flow rate throughout the premenstrual and menstrual periods [ 30 ].…”
Section: Yoga Asana’s and Their Target Benefitsmentioning
confidence: 99%
“…Furthermore, the presence of sex steroid receptors on MCs suggests that sex hormones may exert biological effects through binding to these receptors [135]. Exogenous estrogen and progesterone have both been shown in studies to play a role in PMA management [120,136]. In a prospective study of 106 postpubertal women with asthma, those who used oral contraception (OC) had lower asthma symptoms, better pulmonary function, and better asthma control than those who did not [137].…”
Section: Perimenstrual Asthmamentioning
confidence: 99%